ANALYSIS OF TYPES AND ABUNDANCE OF MICROPLLASTIC IN WATER AND SEDIMENT IN COASTAL WATERS OF PANDAN DISTRICT, CENTRAL TAPANULI REGENCY, NORTH SUMATRA - Yani, Indah Novi; Siregar, Yusni Ikhwan; Amin, Bintal (Asian Journal of Aquatic Sciences, 2021)
This research was conducted in February 2021 in the coastal waters of Pandan District, Central Tapanuli Regency, North Sumatra Province. The purpose of this study was to analyze the type and abundance of microplastics in water and sediment and to determine the relationship between the abundance of microplastics in water and in sediment. The method used in this research is survey method which is carried out by observing and taking samples directly in the field and followed by laboratory analysis. Based on the results of the study, the highest abundance of microplastics in water was 706.67 particles/m³, and in sediments was 14,193.33 particles/kg. The abundance of microplastics in water and sediment did not differ significantly between stations. Simple linear regression test showed that the abundance of microplastics in water had a weak relationship with the abundance of microplastics in sediments.